2002
DOI: 10.1145/511399.511359
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing user behavior and network performance in a public wireless LAN

Abstract: This paper presents and analyzes user behavior and network performance in a public-area wireless network using a workload captured at a well-attended ACM conference. The goals of our study are: (1) to extend our understanding of wireless user behavior and wireless network performance; (2) to characterize wireless users in terms of a parameterized model for use with analytic and simulation studies involving wireless LAN traffic; and (3) to apply our workload analysis results to issues in wireless network deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 15 publications
2
132
0
Order By: Relevance
“…It has been shown that wireless data traffic exhibits selfsimilarity and long-range dependency [6][7][8][9]. While taking into account the self-similar nature of multiservice traffic, it is not mundane to build tight bound SLAs between heterogeneous QoS domains due to the high variability in the offered traffic.…”
Section: All-ip Diffserv Architecture For Wireless Internetmentioning
confidence: 99%
“…It has been shown that wireless data traffic exhibits selfsimilarity and long-range dependency [6][7][8][9]. While taking into account the self-similar nature of multiservice traffic, it is not mundane to build tight bound SLAs between heterogeneous QoS domains due to the high variability in the offered traffic.…”
Section: All-ip Diffserv Architecture For Wireless Internetmentioning
confidence: 99%
“…M2 have to associate with AP2. Supposing that all mobile stations generate the same data traffic, the load distribution across access points will be highly uneven [1]. This can cause a performance degradation perceived by the other stations attached to AP2.…”
Section: General Presentation Of Our Approachmentioning
confidence: 99%
“…One of its popular uses is its cheap hardware infrastructure price promoting to provide practical and efficient Hotspots environment [1]. The research works [1,2] carried in this context had proved that additional effort is yet required to build up a system with a high service quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous measurement studies focused on the domain-level performance, e.g., overall network usage and user mobility patterns [13,14,15,16]. The first attempt to investigating the packet loss and delay characteristics of IEEE 802.11b wireless link is reported in [17], but unfortunately, the analysis was performed at the MAC level, and the tracing was carried out without any background traffic.…”
Section: Related Work and Motivationmentioning
confidence: 99%